Case report for an internet- and mobile-based intervention for internet use disorder - Bernstein, Karina; Zarski, Anna-Carlotta; Pekarek, Emilia; Schaub, Michael Patrick; Berking, Matthias; Baumeister, Harald; Ebert, David Daniel (Frontiers in Psychiatry, 2023)
Background and aims: Internet use disorder (IUD), characterized as the inability to control one’s internet use, is associated with reduced quality of life and mental health comorbidities such as depression, substance abuse, or anxiety. Evidence-based treatment options are scarce due to the novelty of the diagnosis. Internet- and mobile-based interventions (IMI) may be an effective means to deliver psychological treatment to individuals with IUD as they address affected individuals in their online setting. This study presents a newly developed IMI for IUD disclosing treatment satisfaction and preliminary effects by exemplifying with a case report. Methods: The case of a female participant with IUD, characterized by an excessive use of social media, is analyzed. The case report follows the CARE guidelines and presents qualitative and quantitative outcomes regarding potential symptom reduction measured by the Internet Addiction Test (IAT) and Compulsive Internet Use Scale (CIUS), treatment satisfaction measured by the Client Satisfaction Questionnaire (CSQ) and feasibility by analyzing participant’s written feedback during treatment. Results: The case report shows that internet- and mobile-based interventions may be feasible in supporting an individual in reducing symptoms of IUD as well as depressive symptoms, anxiety and procrastination behavior. Treatment satisfaction was reported as good. Discussion and conclusions: This case report illustrates that IMIs can have the potential to be an easily accessible and possibly effective treatment option for IUD. Case studies on IMIs may provide insights into important mechanisms for symptom change. Further studies are needed to expand our understanding of this diverse disorder to provide adequate treatment. Clinical Trial Registration: https://clinicaltrials.gov/,DRKS00015314.
CRIS-Team Scopus Importer:2023-08-18
Keywords: case report; internet use disorder; internet- and mobile-based intervention; social media use; student